Anomalous mechanical behavior in NiMnGa alloy sintered through open die pressing method. (March 2023) - Villa, Francesca; Morlotti, Andrea; Fanciulli, Carlo; Passaretti, Francesca; Albertini, Franca; Villa, Elena
Abstract: NiMnGa Heusler system has attracted attention principally thanks to its extremely large magnetic-field-induced strain caused by the rearrangement of the twin boundaries induced by an applied magnetic field. Moreover, the microstructure of polycrystalline NiMnGa alloys has been investigated to improve the functional properties and to reduce their typical brittleness. For this reason, increasing interest has been devoted to different kinds of fabrication routes for this material. In the present study, Ni50 Mn30 Ga20 alloy was produced by means of the open die pressing (ODP) process. This sintering method was implemented as an alternative and low-cost method for the consolidation of NiMnGa powders. The effects of the thermo-mechanical processing were investigated and correlated to the NiMnGa functional properties. The material characterization was conducted by means of optical microscopy, differential scanning calorimetry and mechanical analysis, including strain recovery tests and dynamic mechanical thermal analysis. In this way, the physical characterization of the NiMnGa sintered alloy allowed a complete investigation of the evolution of the thermoelastic martensitic transition (TMT). Moreover, a correlation between thermomechanical condition and functional properties was possible and an anomalous trend in the mechanical response of the material was observed due to the presence of stored energy originated from the sintering process. In addition, magnetic susceptibility measurements provided a preliminary characterization of the magnetic transition of the alloy and the effects of the sintering process on the magnetic properties were observed. This experimental study is the starting point for the implementation of an alternative production method for polycrystalline NiMnGa and for the optimization of the coupling between structural and magnetic order thanks to the combination of the structural and magnetic transitions. Graphical Abstract: ga1